Flora and structure of the secondary vegetation after the use of different crushers - Rodrigues, Mauro Antônio Cavaleiro Macedo; Miranda, Izildinha Souza; Kato, Maria do Socorro Andrade (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this study was to characterize and compare the structure of secondary forests with four years of age, in the northeast of Pará State, which were formed after use of the crushers Ahwi FM600 (T1) and Tritucap (T2). The study was accomplished in five areas of small producers, each one were divided in plots with 60 m² for study area. The mean diversity (H') was 2.84 for T1 areas and 2.95 for T2 areas; mean density was 530,167 ind. ha-1 in T1 and 459,556 ind. ha-1 in T2; mean basal area of T1 was 1.25 m² ha-1 and 4.55 m² ha-1 for T2; estimate dry biomass for T1 was 2.37 t ha-1 and 6.68 t ha-1 for T2. There are structural differences on secondary forests formed after the use of both crushers.
Keywords: Amazonia; agriculture; slash; biomass